2015
DOI: 10.3399/bjgp15x687673
|View full text |Cite
|
Sign up to set email alerts
|

Weekend opening in primary care: analysis of the General Practice Patient Survey

Abstract: BackgroundSeven-day opening in primary care is a key policy for the UK government. However, it is unclear if weekend opening will meet patients' needs or lead to additional demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
1
16
0
2
Order By: Relevance
“…However, a recent British Journal of General Practice survey found that, out of 881,183 patients, 80.9% reported no problems with current opening times. (14) This suggests that most patients find no need for this measure. As such, the question remains whether this option would alleviate the stress on secondary care.…”
Section: The British Student Doctormentioning
confidence: 99%
“…However, a recent British Journal of General Practice survey found that, out of 881,183 patients, 80.9% reported no problems with current opening times. (14) This suggests that most patients find no need for this measure. As such, the question remains whether this option would alleviate the stress on secondary care.…”
Section: The British Student Doctormentioning
confidence: 99%
“…However, the article by Ford and colleagues provides timely new evidence on this controversy. 5 The responses of over 880 000 patients Access to primary care: creative solutions are needed editorials "... access, a crucial dimension of primary care, has become a political and professional battlefield ..." participating in the General Practice Patient Survey 2014 show that most patients do not think they need weekend opening, although Ford and colleagues conclude that it may benefit certain patient groups, such as younger people in full-time work. They also comment that Sunday opening, in addition to Saturday, is unlikely to improve access.…”
Section: Seven-day Workingmentioning
confidence: 99%
“…The inverse care law is also the subject of a study conducted by McLean and colleagues, 5 who analysed levels of multimorbidity, patient consultation rates, and practice payments in relation to measures of deprivation in 956 general practices in Scotland. A weak relationship was demonstrated between multimorbidity and consultation rates, with much steeper gradients when consultation rates were related to deprivation.…”
Section: Deprivation and Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…And when general practitioners tried a pilot of working on Sundays, it failed because of a lack of both staff and patients 11. Moreover, a large survey of primary care patients demonstrated only lukewarm enthusiasm for weekend opening 12. It seems that people do want urgent healthcare at weekends but not always of the type that they believe is available in primary care, especially on Sundays.…”
mentioning
confidence: 99%